Pendidikan Seni Musik sebagai Strategi Penanaman Nilai Demokrasi dan Toleransi di Sekolah Dasar - Ardi, Ridwan (Journal of Character and ELementary Education, 2025)
Instilling democratic and tolerance values ​​from an early age is an urgent need in forming a generation that is able to live peacefully amidst diversity. Elementary schools, as the foundation of character education, have an important role in internalizing these values ​​through various approaches, one of which is through music education. This literature study aims to explore how music arts education can be an effective strategy in instilling democratic and tolerance values ​​in elementary school environments. This study examines various national and international literature sources related to the relationship between music activities, student collaboration, and character building. The results of the study show that participatory music activities, such as ensembles, choirs, and collaborative compositions, create a space that encourages cooperation, equal roles, mutual listening, and appreciation of differences. In addition, traditional music from various regions taught in schools also strengthens appreciation for cultural diversity and values ​​of tolerance. Music arts education not only trains artistic skills, but also becomes a strong social and emotional medium in building empathy and openness between students. This study recommends strengthening music learning policies in elementary schools as part of character education, especially in forming democratic and tolerant citizens. It is expected that the results of this study can be a reference for educators and policy makers to design an integrative curriculum between arts education and values ​​education.